Efficacy and safety of alemtuzumab versus fingolimod in RRMS after natalizumab cessation - Pfeuffer, Steffen; Schmidt, René; Straeten, Frederike Anne; Pul, Refik; Kleinschnitz, Christoph; Wieshuber, Marinus; Lee, De-Hyung; Linker, Ralf; Doerck, Sebastian; Straeten, Vera; Windhagen, Susanne; Pawlitzki, Marc; et al. (Journal of neurology, 2019)
BackgroundNatalizumab (NTZ) was the first approved monoclonal antibody for the treatment of relapsing-remitting multiple sclerosis (RRMS). Despite proven and sustained efficacy, its use is limited by the risk of progressive multifocal leukoencephalopathy (PML). Moreover, some patients show ongoing disease activity under NTZ, requiring a switch to another disease-modifying treatment (DMT). However, evidence regarding the optimal DMT for treatment of active RRMS after NTZ-cessation is still scarce.ObjectiveTo evaluate efficacy and safety outcomes of ALEM vs FTY treatment after cessation of NTZ.MethodsWe retrospectively identified patients at 12 German neurology centers and analyzed risks for disease activity, adverse events, disability progression, and treatment discontinuation.Results195 patients were identified and 144 underwent final analysis (FTY: 101; ALEM: 42). The hazard ratio for clinical relapses was 2.24 favoring ALEM (95% CI 1.12-4.50; p = 0.015). The hazard ratio for adverse events was 7.78 (95% CI 1.04-57.95; p = 0.006) and 2.41 for MRI progression (95% CI 1.26-4.60; p = 0.004). The odds ratio for disability progression after 12 months was 4.84 (95% CI 1.74-13.47, p = 0.003). Differences remained after adjusting for possible confounders (e.g., age, sex, baseline disability, NTZ treatment duration, washout time).ConclusionOur findings indicated particular advantages of ALEM compared to FTY in patients stopping NTZ.
Published online: 16 November 2018
Gesehen am 10.07.2019